Design of Internet/Iptv Television System Web-Based On Local Community Network - Ari Waluyo (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2020)
>Internet Protocol Television / IPTV is a system used to transmit multimedia data over an Internet Protocol (IP) based network. This technology is changing the way humans communicate with television to be more interactive. IPTV is a technology that is being developed in various countries, including Indonesia, which will soon implement it. The existing broadcast system on Kebumen TV still uses analog transmitters using UHF frequencies, so broadcasts cannot reach large areas and are still limited by broadcast time schedules. The development of a TV transmitter system made is a solution to solve existing problems. The TV transmitter system created will utilize the Internet Protocol (IP) network so that Kebumen TV viewers who are outside the broadcast range can enjoy Kebumen TV broadcasts. Internet Protocol Television (IPTV) is a method of channeling television images and sound through the Internet Protocol (IP). The feature of IPTV is that it can broadcast live or pre-recorded digital video and can transmit programs from various sources. From the research results of television transmitters using the Internet Protocol (IP) network have several advantages compared to analog tv transmitters, among others nois produced far less, is cheaper, and allows for broadcasting more functions and broadcast content.